Reproductive performance of Kittlitz's Murrelet in a glaciated landscape, Icy Bay, Alaska, USA - Kissling, Michelle L.; Gende, Scott M.; Lewis, Stephen B.; Lukacs, Paul (ScholarWorks at University of Montana, 2015)
Kittlitz's Murrelet (Brachyramphus brevirostris) is a dispersed-nesting seabird endemic to Alaska and eastern Russia that may have experienced considerable population declines in some parts of its range in the past few decades. Poor reproduction has been suggested as the demographic bottleneck, yet there are no direct estimates of reproduction in a glaciated area where this species reaches its highest densities at sea during the breeding season. The lack of demographic information in glacial habitats has limited our ability to interpret population trends and to clarify whether the presence of glaciers affects reproductive performance. Between 2007 and 2012, we radio-tagged Kittlitz's Murrelets to measure breeding propensity, nesting success, and fecundity in the heavily glaciated landscape of Icy Bay, Alaska, USA. Of 156 radio-tagged birds, 20% were breeders, 68% were potential breeders, and 12% were nonbreeders. Radio-tagged males (29%) were more likely to be breeders compared to females (11%). Across all years, we located 34 Kittlitz's Murrelet nests, 38% of which were successful. Daily nest survival probability (± SE) was 0.979 ± 0.005, with most nests failing during incubation; if extrapolated to a 55-day period from nest initiation to fledging, the nest survival rate was 0.307 ± 0.083. Low fecundity was due largely to low breeding propensity, not low nesting success. For context, we also determined the breeding status of 14 radio-tagged Marbled Murrelets (B. marmoratus), most of which were breeders (79%) and successfully fledged young (69%). Our data demonstrated that Kittlitz's Murrelets were outperformed in all facets of reproduction compared to Marbled Murrelets. Low fecundity estimates for Kittlitz's Murrelet were consistent with a 10% per annum decline in Icy Bay between 2002 and 2012, suggesting that poor reproductive performance contributed to the local population decline of this species.